Comparing the effect of humanoid and human face for the spatial orientation of attention - Chaminade, Thierry; Okka, Maria M. (Frontiers in Neurorobotics, 2013)
The current study was designed to investigate how the automatic spatial orientation of attention induced by the perception of another agent's orientation of attention is modulated by the social nature of the other agent. Modified versions of the Posner task, using a real or schematic face with eyes or head looking toward the left or the right before a to-be-detected target appears on one side of the screen have been used to demonstrate a reduction of reaction time (RT) for target detection when the gaze is directed toward the target, even though the cue is not informative. We compared the effect of two agents, the humanoid robotic platform Nao and a real human, using head turn to cue the spatial orientation of attention. Our results reproduced the typical Posner effect, with reduced RT to valid compared to invalid spatial cues. RT increased when no spatial information was provided, interpreted as an increased difficulty to disengage from a direct gaze. RT was also increased when the robot was used instead of the human face and when the eyes of the stimuli were blacked out. Both effects were interpreted as resulting from an increased difficulty to disengage attention from the central stimulus because of its novelty. In all experiments, there was no interaction between cue validity and cue agent, implying that the exact nature of the human-like agent didn't have an effect on the automatic spatial orientation of attention. Altogether, our results imply that a humanoid face is as potent as a human face to trigger an automatic orientation of spatial attention.